Effects of preservation of rumen inoculum on volatile fatty acids production and the community dynamics during batch fermentation of fruit pomace. (February 2021) - Njokweni, Sesethu G.; Weimer, Paul J.; Botes, Marelize; van Zyl, Willem H.
Highlights: In vitro digestion of pomace with DMSO cryo-rumen fluid is similar to fresh rumen. Extraruminal fermentations with glycerol cryo-rumen lead to elevated VFA yields. Fermentation products of DMSO cryo-rumen have distribution similar to fresh rumen. Unweighted unifrac distance metrics clustered DMSO cryo-rumen with fresh rumen. Abstract: Rumen fluid (RF) as inocula is useful for evaluating biomass digestibility and has potential for producing volatile fatty acids (VFA) via the carboxylate platform. However, RF is not readily available, necessitating evaluation of potential preservation methods. Glycerol (50% v/v) and DMSO (5% v/v) were used to preserve rumen inocula for 3 months at −80 °C. Effects of cryo-preservation on digestibility, VFA production and community composition with β-diversity distance metrics were compared to fresh RF using apple, citrus and grape pomace as substrates. For all substrates, DMSO cryo-preserved rumen digestibility parameters, VFA yield and product distribution were more significantly comparable to fresh RF ( P > 0.05) than was glycerol cryo-preserved RF. Similarly, β-diversity coefficient (unweighted unifrac) between DMSO cryo-preserved RF and fresh RF was 0.250 while the coefficient was 0.359 for the glycerol cryo-preserved RF compared to fresh RF. This showed that a DMSO cryo-preserved RF is less affected by preservation effects and is a more promising alternative to fresh RF.